TEN REASONS WHY OPERATING DEPARTMENT PRACTITIONERS AND THEATRE NURSES MIGHT NOT WANT TO QUOTE OR CITE FROM THIS ARTICLE - Pennington, Bernard (Operating Room Nurses Association of Canada Journal, 2010)
Academic writing can fill pre- and postregistration students with fear and dread. Students often construct written work around re-worded passages from their sources. This results in poor quality work, low marks and frustration. The aim of this article is to inform students embarking on courses in higher education about what academic writing is – and equally importantly what it is not.